Analisis Kebutuhan E-LKPD Terhadap Pembelajaran Fisika Di Masa Pandemi Covid-19 - Salma Tua Nababan; Desy Hanisa Putri (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2022)
The Purpose of the research to analyze the needs of an appropriate in physics learning E-LKPD, the Covid-19 pandemic era. The research used a qualitative descriptive method. This research was conducted at SMA Negeri 4 Bengkulu City. The research subjects are students, teachers, and vice headmaster of curriculum. Collecting data using questionnaires and interview guidelines. Data analysis used Miles-Huberman. The data validity technique uses source triangulation. The Result of research provides several conclusions that no E-LKPD is suitable for online learning during the Covid-19 pandemic era, so it is necessary to develop an E-LKPD that is following the Covid-19 emergency curriculum. E-LKPD in question is E-LKPD which can improve students' critical thinking skills with inquiry learning models or problem-based learning (PBL).